2018
DOI: 10.1525/jps.2018.47.4.30
|View full text |Cite
|
Sign up to set email alerts
|

Owning the Homeland: Property, Markets, and Land Defense in the West Bank

Abstract: This article examines the formation of land defense in relation to changing legal and economic conditions in the occupied Palestinian territories. It argues that as a result of settler capital and law, Palestinian land defense should be understood as emerging through, rather than apart from, private property. Specifically, it explores how private property and market forces shaped agrarian land defense (1970s-1980s) and real estate land defense (post-2007). In the 1970s and the 1980s, land defense sought to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…But unlike these settlers, Palestinians do not have recourse to the rights and promises of citizenship, and ownership is thus always permanently provisional. Finally, this living archive encompasses a century of land struggle against Zionist colonization, both before and after the foundation of the state of Israel (Kohlbry 2018). The 1970s and 1980s were a distinct conjuncture, and the surveyors were part of a broader land‐defense effort that drew on past experience and transformed it to confront the specific ways that colonization was then taking shape in the West Bank.…”
Section: The Living Archive Of Land Defensementioning
confidence: 99%
“…But unlike these settlers, Palestinians do not have recourse to the rights and promises of citizenship, and ownership is thus always permanently provisional. Finally, this living archive encompasses a century of land struggle against Zionist colonization, both before and after the foundation of the state of Israel (Kohlbry 2018). The 1970s and 1980s were a distinct conjuncture, and the surveyors were part of a broader land‐defense effort that drew on past experience and transformed it to confront the specific ways that colonization was then taking shape in the West Bank.…”
Section: The Living Archive Of Land Defensementioning
confidence: 99%
“…It involves state expropriation (Levien 2018; Rabie 2021) as well as threats and indirect pressure (Fogelman and Bassett 2017; Lund 2020). Because land in these areas is often devalued, large‐scale acquisitions have the effect of raising prices and incorporating local people as active, if not always willing, participants in emerging land markets (Kohlbry 2018; Levien 2018).…”
Section: Making Land Investablementioning
confidence: 99%
“…It was striking, when I visited again in 2022, that the price was something that people still remembered. Second, as was the case for Rawabi (Rabie 2021), people reported that the use of brokers kept the extent of sales hidden in the beginning (Harb 2020; Kohlbry 2018). Doing so kept prices down, and it was not a popular tactic.…”
Section: Private Enclaves In the Highlandsmentioning
confidence: 99%